2001
DOI: 10.1002/1521-3773(20010401)40:7<1258::aid-anie1258>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Acidic and High-Temperature Hydrothermally Stable Mesoporous Aluminosilicates with Ordered Hexagonal Structure

Abstract: Self‐assembly of preformed aluminosilicate nanoclusters in the presence of templating micella provides a route to strongly acidic, hydrothermally stable mesoporous aluminosilicates with ordered hexagonal structures (MAS‐5). Results show that the materials are similar to Beta zeolite and are highly active for the catalytic cracking of 1,3,5‐triisopropylbenzene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(105 citation statements)
references
References 27 publications
0
105
0
Order By: Relevance
“…ZIF-8 thus was further probed and shown to be unchanged for up to 24 h in 0.1 and 8 M aqueous sodium hydroxide at 100°C. We note that the hydrothermal stability of ZIF-8 is superior to those of original MCM and SBA types of ordered mesoporous silica (17), even rivaling the ultrastable derivatives of these materials (20).…”
Section: Resultsmentioning
confidence: 99%
“…ZIF-8 thus was further probed and shown to be unchanged for up to 24 h in 0.1 and 8 M aqueous sodium hydroxide at 100°C. We note that the hydrothermal stability of ZIF-8 is superior to those of original MCM and SBA types of ordered mesoporous silica (17), even rivaling the ultrastable derivatives of these materials (20).…”
Section: Resultsmentioning
confidence: 99%
“…Because thermal treatment (>373 K) may destroy the pore system of MCM-41 by either dealumination or coking, [40][41][42] the stability of the Pt/MCM-41…”
mentioning
confidence: 99%
“…Figure 7 shows FT-IR spectra of intermediate samples such as M, MHT, and MHT8.5HT. It is reported that IR bands in the 420-500 cm -1 region and those between 520 and 600 cm -1 are assigned to internal tetrahedron vibrations such as 6-and 5-rings of T-O-T (T = Si or Al) in zeolites [28]. These IR bands for clinoptilolite and zeolite-P were observed between 430 and 604 cm -1 [29,30].…”
Section: Structural Parametersmentioning
confidence: 99%
“…Several research groups have attempted to use tiny zeolite precursors or secondary building units of synthetic zeolites as starting materials for the preparation of mesoporous materials [3][4][5][6][7][8][9]. Mesoporous materials with moderate acidic properties originated from zeolite precursors have been synthesized from nanoclusters of zeolite Y, zeolite Beta and ZSM-5 [3][4][5][6]9]. Synthesis of hydrothermally stable mesoporous molecular sieves from zeolite mordenite and zeolite L were also reported [7,8].…”
Section: Introductionmentioning
confidence: 99%